Teaching Strategies in Writing Class at Palopo Cokroaminoto University - Juwita Crestiani M (Institut Agama Islam Negeri Palopo, 2019)
This research deals with the teaching strategies used by the lecturers in writing class at Palopo Cokroaminoto University. The population of this research was lecturers of primary school teacher education of Palopo Cokroaminoto University. The total numbers of the population are 20 lecturers. The researcher used purposive sampling and chose one lecturer in the third semester as the sample because the lecturer taught writing subject and often use various strategies in teaching writing. The instruments in this research were observation checklist, recording and interview. The researcher used observation checklist and recording in the class when the lecturers taught writing. The researcher found the lecturer used two strategies in teaching English writing namely lecturing strategies and active learning. Active learning such us, the lecturer uses media in explaining material, giving question to the students to encourage their motivation, create an enjoyable atmosphere to make students more creative in producing writing, analyzing and doing assessment about students’ work, giving motivation to the students for making a report such as composition. Lecturing strategies such us, preparing the media, explaining the material, help and encourage the students to attention and listen accurately, the teacher can use her/his experience in teaching or explaining material especially in giving an example, make a conclusion of the materials.